An Overview of Nursing and Physiotherapy Informatics: Practices and Perspectives in Saudi Arabia - Nayta, Hisham Taha; ALMANSOUR, MANIE NASSER A; Aljabali, Ghaliah Abdullah; alharbi, Hanan Mohammed; Almutairi, Reem Ageel; Al-Rubaie, Hussein Mufleh Hassan; Alabass, Mohammed Abdullah Yahia; Al Abbas, Raed Hadi Muhammad; AL DUBAYS, FAHAD MOHMMAD ZIDAN; ALYAMI, SAIDAN MOHAMMED B (Journal of Ecohumanism, 2024)
Nursing and physiotherapy informatics have emerged as essential fields in the evolving landscape of healthcare, enabling the efficient management of patient data, improving care delivery, and enhancing treatment outcomes. In Saudi Arabia, the integration of informatics within these professions remains an ongoing challenge, with both fields showing considerable potential for growth in terms of technology adoption and application. This narrative review examines the current state of nursing and physiotherapy informatics in Saudi Arabia, exploring the historical development, definitions, and scope of each discipline. It highlights the advantages and challenges associated with their implementation, including the need for structured education, training programs, and policy support. Despite the growing recognition of the role of informatics in healthcare, barriers to full integration persist, particularly in the fields of physiotherapy and nursing. The review proposes strategies for overcoming these challenges, including fostering a culture of informatics, improving technological infrastructure, and advancing research in these areas. Ultimately, the goal is to enhance patient safety, improve healthcare outcomes, and ensure the efficient delivery of care through the strategic implementation of informatics systems in nursing and physiotherapy practice in Saudi Arabia.